Emerging financial centres - Beate Reszat (Hamburg Institute of International Economics (HWWA), 1998)
As emphasised in the beginning, the considerations presented here are very preliminary by nature. Nevertheless, some of the aspects discussed seem worth summarising. First, financial markets worldwide show a tendency of asymmetric regional " clustering" with newly emerging places challenging the dominant position of the traditional centres. The question is if and to what extent these developments can be explained by processes of spacial self-organisation and evolution. It has been argued that an insufficient analytical and empirical foundation forbids drawing the analogy to the natural sciences too far and the prerequisites for theorising about those processes had been outlined. Financial markets can be regarded as emergent, self-organising systems. They are characterised by a high degree of complexity and a large "population" of actors, whose individual behaviour and strategies can no longer be traced but whose interactions result in the emergence of order and structure on the system level. They are able to create a market "culture" which allows a place to become an international centre. For this culture to emerge, and for banks and other institutions from all over the world to locate in this place, several conditions have to be met. Theories of self-organisation emphasise the existence of repellent and attracting forces which must come together in a certain way for emergent qualities in the aggregate to evolve. The main challenge for further research will be to identify those factors, to explain the ways in which they influence the rise and decline of markets and to exploit the scope for policy action. Self-organising economic systems may not allow building models as design for "basic ideas" or to forecast the future. But, they may offer rich insights to those studying them in detail. So far, little research on the determinants of the location of international financial activities has been done, and the influences and mechanisms behind the rise and fall of markets are poorly understood. Given the present dramatic changes in the world financial system, every attempt to enhance the understanding of its functioning seems worth the effort.
Keywords: 330; Finanzplatz; Internationaler Finanzmarkt; Wirtschaftsgeographie; Raumwirtschaftstheorie; Bioökonomik; Evolutionsökonomik; Theorie; Welt